The Effect of Using English Movie in Teaching Simple Present Tense to Seventh Grade Students of Smp Plus Melati Samarinda in Academic Year 2017/2018 - M. Luqman Al Fatih (E3L: Journal of English Language Teaching, Linguistics, and Literature, 2018)
Watching movie, especially English movie is very useful for students who are learning English because not only as something enjoyable and entertainment, but also as a motivation for learning English. The purpose of this research was to find out whether there is any significant effect of using English movie in teaching simple present tense to seventh grade student of SMP Plus Melati Samarinda or not. The design of this study was pre-experimental design consisting of one group pre-test and post-test by selecting 23 students as sample. The research instrument was simple present test in multiple choice forms. In analyzing the data, the researcher used the Mean score and the paired sample t-test by using program SPSS 0.21. The t-test was used to measure the hypotheses testing. The findings of this research showed that (1) the total score of pre-test was 1216 with mean score 52.87 which was categorized as poor (2) the total score of Posttest was 1488 with mean score 64.70 which was categorized as fair. From the result of the pre-test and posttest we can see that there was significant difference between teaching simple present before and after using English movie as a media. (3) From the Hypotheses Testing of Paired sample T-test using SPSS program, it showed that the value sig. (2-tailed) < α or 0.000 < 0.05. The value sig. (2-taliled) was higher than the value of 0.05. It means that the Null Hypothesis (Ho) was rejected and the Alternative Hypotheses (Ha) was accepted. It means that there was a significant effect of using English movie in teaching simple present tense to seventh grade students of SMP Plus Melati Samarinda. Based on the result of this research, it can be inferred that there was a significant effect of using English movie in teaching simple present tense.